Electrochemotherapy for head and neck cancers: possibilities and limitations - Morozas, Arnoldas; Malyško-Ptašinskė, Veronika; Kulbacka, Julita; Ivaška, Justinas; Ivaškienė, Tatjana; Novickij, Vitalij (Frontiers in Oncology, 2024)
Head and neck cancer continues to be among the most prevalent types of cancer globally, yet it can be managed with appropriate treatment approaches. Presently, chemotherapy and radiotherapy stand as the primary treatment modalities for various groups and regions affected by head and neck cancer. Nonetheless, these treatments are linked to adverse side effects in patients. Moreover, due to tumor resistance to multiple drugs (both intrinsic and extrinsic) and radiotherapy, along with numerous other factors, recurrences or metastases often occur. Electrochemotherapy (ECT) emerges as a clinically proven alternative that offers high efficacy, localized effect, and diminished negative factors. Electrochemotherapy involves the treatment of solid tumors by combining a non-permeable cytotoxic drug, such as bleomycin, with a locally administered pulsed electric field (PEF). It is crucial to employ this method effectively by utilizing optimal PEF protocols and drugs at concentrations that do not possess inherent cytotoxic properties. This review emphasizes an examination of diverse clinical practices of ECT concerning head and neck cancer. It specifically delves into the treatment procedure, the choice of anti-cancer drugs, pre-treatment planning, PEF protocols, electroporation electrodes, as well as the efficacy of tumor response to the treatment and encountered obstacles. We have also highlighted the significance of assessing the spatial electric field distribution in both tumor and adjacent tissues in prior to treatment as it plays a pivotal role in determining treatment success. Finally, we compare the ECT methodology to conventional treatments to highlight the potential for improvement and to facilitate popularization of the technique in the area of head and neck cancers where it's not widespread yet while it is not the case with other cancer types.